Character education trend in Indonesia - Mohamad Joko Susilo; Mohammad Hajar Dewantoro; Yuningsih Yuningsih (Journal of Education and Learning (EduLearn), 2022)
Character education is an educational concept to form and foster a Muslim personality as a whole (syumuliyah). This literature study aimed to determine the implementation of character education and supporting and inhibiting factors for the implementation of character education in formal schools in Indonesia. Data analysis techniques by means of data reduction, data display, and conclusion. Based on research findings, the trend of implementing character education in Indonesian formal schools has the same spirit in the content of character education. In formal schools with the status of public schools, the implementation of character education follows government regulations as stated in the Strengthening of Character Education (SCE), which is an implication of Islamic teachings. As for formal schools with private status on an Islamic basis, character education tends to be oriented towards cultivating akhlakul karimah (moral education) combined with government regulations. The implications of this research lead to the cultivation of character values that are embedded in social attitudes and spiritual attitudes as provisions for students' daily lives. The supporting and inhibiting factors for the implementation of character education are also discussed.